Chest Therapy sebagai Media Intervensi Fisioterapi Suplemen Bagi Anak dengan Kondisi Common Cold di Kelurahan Setabelan - Atikah Nurulinsani; Farid Rahman (Pusat Riset dan Inovasi Nasional, 2023)
Common cold is an Upper Respiratory Tract Infection (URI) that often occurs in babies and children. The World Health Organization states that the incidence of URI in developing countries with under-five mortality rates above 40 per 1000 live births is 15% -20% per year at the age of under five. In Indonesia, 14% of under-five deaths are caused by the common cold. The prevalence of children under five getting the common cold in Indonesia is estimated at 3 to 6 times per year. Mitra's description showed that there was a high number of children aged 1-4 years who experienced the common cold in the last 3 months at the Setabelan Community Health Center, totaling 135 children. The aim of the activity is to increase parents' understanding and attitudes in dealing with children who suffer from the common cold. The method used was a lecture and discussion method using leaflet media accompanied by a demonstration of sputum removal techniques and evaluating community knowledge and understanding with pre-tests and post-tests carried out by the Setabelan Village community. The counseling received a positive response from the children's parents with an increase in post-test scores and the emergence of skills in sputum removal techniques.